The impact of Ming and Qing dynasty maritime bans on trade ceramics recovered from coastal settlements in northern Sumatra, Indonesia. (March 2020) - Tai, Yew Seng; Daly, Patrick; Mckinnon, E. Edwards; Parnell, Andrew; Feener, R. Michael; Majewski, Jedrzej; Ismail, Nazli; Sieh, Kerry
Abstract: We review published literature and historical texts to propose that three periods of official Chinese maritime bans impacted the composition and circulation of trade ceramics along Asian trade routes: Ming Ban 1 (1371 – 1509), Ming Ban 2 (1521 – 1529), and Qing Ban (1654 – 1684). We use ceramics collected during a landscape archaeology survey along 40km of coast in Aceh, Indonesia to show how the three ban periods manifest in the ceramic record of settlements along an important stretch of the maritime silkroad. All three ban periods overlap with reductions in the quantity of Chinese ceramics. Within several decades of the start of Ming Ban 1, people in Aceh began importing ceramics from production centers in Burma and Thailand as a substitute for Chinese ceramics. Following Ming Ban 2, there is an increase in imports from Chinese production centers, albeit from new kilns sites. While brief, the Qing ban resulted in an almost immediate influx of ceramics from Japan and Vietnam, which maintained some market share until the mid-17th century, after which Chinese ceramics dominate the record until the end of the Qing dynasty. Our data show both the importance of Chinese ceramics within regional trade networks and how those networks and local patterns of consumption adapted to disruptions of supply.